Optimized design of the restrictor for a MEMS thermal gas flowmeter. (1st October 2022) - Yang, Zhi; Zhai, Yuan; Deng, Bo; Yin, Hao; Lu, Zhuang; Xiang, Yi; Shi, Jinliang; Zeng, Zhijie; Wu, Ying
Abstract: To improve the linear range of measurement, a restrictor is usually added to the main flow channel of a capillary-tube-type thermal mass flowmeter. However, as the linear range of the flowmeter increases, the singularity will occur in the low mass flow velocity section of the flowmeter calibration data, which will lead to a significant decrease in the measurement accuracy in this section. To address this issue, first, this paper developed a microelectromechanical system (MEMS) thermal gas flowmeter based on the principle of capillary-tube-type thermal mass flow. Then, the effect of the bypass ratio on its performance was further investigated using quantitative analysis and was verified using Fluent numerical analysis. In addition, to explain the singularity, the bypass ratio-sensitivity relationship model was built. Based on this model, the bypass ratio can be changed by adjusting the restrictor parameters to optimize the performance of the MEMS thermal gas flowmeter. Moreover, six numerical simulation models of restrictors with different aperture diameters and aperture numbers were designed. The numerical analysis results show that within a certain range of aperture diameters and aperture numbers, the singularity is more easily weakened when the aperture diameter decreases or the aperture number increases. Finally, the restrictor with the optimum aperture number and suitable aperture diameter was selected as the test model for calibration, and the goodness of fit R 2 of the calibration results is improved from 0.9937 to 0.9972, the singularity in the low mass flow velocity section is significantly weakened, and the sensitivity is improved.